Advance Flood Inundation Model Toward Flood Nowcasting: A Review - Kadir M.A.A.; Zainol M.R.R.M.A.; Luo P.; Kaamin M.; Yahya S.N.H.S. (Universiti Malaysia Perlis, 2023)
Flood nowcasting is a short time prediction (usually less than 3 h) of the spatial and temporal evolution of flood inundation. Typical flood nowcasting consists of several elements, namely data collection system, rainfall forecasting, flood simulation tools, decision support tools and warning process system. Many studies related to the nowcasting system focused on rainfall forecasting but lack of attention towards the flood simulation tool (also known as flood inundation model) in the nowcasting system. This paper reviews the theoretical and functional basis of the recent flood inundation model to meet the need of the flood nowcasting system. The discussion includes factors that contribute to the performance and capabilities of the flood inundation simulation, comparisons of some models, issues in flood inundation modeling related to the flood nowcasting system and future prospects of the flood inundation model. 2022, Universiti Malaysia Perlis. All rights reserved.